Nietzsche's aesthetic turn : reading Nietzsche after Heidegger, Deleuze, and Derrida - Winchester, James J. (SUNY series in contemporary continental philosophy., 1994)
"This clearly written book, intended for both specialists and nonspecialists, focuses on Nietzsche's later writings, where he appears unsystematic and indifferent to questions of truth. "This book undertakes three important and related tasks. The first is a comprehensive analysis of Nietzsche's notoriously slippery writings; the second is a critique of several major positions in Nietzsche interpretation; and the third is a proposal for a kind of philosophizing 'beyond the truth standard, ' a philosophy without nostalgia for the lost grounds of truth. These topics are important today, and form the basis for a considerable debate about the significance of Nietzsche in particular and his role in shaping the twentieth century in general."--Book cover